Analysis of The Influence of Service Quality on Customer Satisfaction and Its Impact on Reuse Intention of Mobile Banking Payment in E-Commerce Transactions - Susanto Susanto; Farid Wahyudi; Swasta Bangun; Tanti Widia Nurdiani; Hery Purnomo (Institut Riset dan Publikasi Indonesia, 2023)
This study intends to determine how consumer satisfaction with mobile banking services affects repurchase interest. Customers of Jabodetabek who utilize mobile banking make up the study's sample. Purposive sampling was used in this investigation, and a non-probability sample of 100 participants was used. Questionnaires will be used by researchers to collect data. The structural equation method of partial least squares, or SEM-PLS, is employed in this study. Higher-order formative and lower-order reflecting constructs were utilised in this study. According to the study's findings, the level of mobile banking services directly affects repurchase interest. The effectiveness of mobile banking services directly affects how satisfied customers are. Repurchase interest is directly influenced by customer satisfaction. Customer satisfaction has an indirect impact on repurchase interest through the quality of mobile banking services. Customer interest in repurchasing mobile applications for e-commerce payment services is influenced by service quality. Customers will be satisfied with good service quality in mobile applications, particularly in e-commerce payment services. It has been demonstrated that the positive indirect effect of mobile banking services is moderated by customers' satisfaction with e-commerce payment services provided by mobile banking.